2020
DOI: 10.1155/2020/2181685
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Drug Prophylaxis for Lens Capsule Opacification after Cataract Surgery

Abstract: Phacoemulsification combined with intraocular lens (IOL) implantation is the international standard operation procedure for cataract and has been generalized worldwide. However, lens capsule opacification, one of the common complications after cataract surgery, impacts the recovery of patients’ visual function to a large extent. Lens capsule opacification has two types, anterior capsule opacification (ACO) and posterior capsule opacification (PCO), according to the location. There is not an accepted ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…The optic edge seems to play a major role in developing anterior capsular opacification (ACO) and PCO, two types of lens capsule opacification according to the location [ 101 ]. In contrast to round-edged optic, modified square-edged led to less PCO and Nd:YAG laser capsulotomy rates [ 102 ] but slightly more ACO perhaps due to impact the LECs' migration path from anterior capsular by cell contact inhibition of sharp edge [ 103 ].…”
Section: Cataract Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optic edge seems to play a major role in developing anterior capsular opacification (ACO) and PCO, two types of lens capsule opacification according to the location [ 101 ]. In contrast to round-edged optic, modified square-edged led to less PCO and Nd:YAG laser capsulotomy rates [ 102 ] but slightly more ACO perhaps due to impact the LECs' migration path from anterior capsular by cell contact inhibition of sharp edge [ 103 ].…”
Section: Cataract Extractionmentioning
confidence: 99%
“…CCS is defined as an exaggerated reduction in anterior capsulectomy and capsular bag diameter after extracapsular cataract surgery [ 124 ] ( Figure 3 ). The fibrotic reaction of residual LECs associated with ACO [ 101 ] and extracellular matrix (ECM) disorder might together work on CCS's pathogenesis in RP [ 34 , 68 , 123 , 124 ]. Recently, a new potential target of stimulating LEC proliferation, tenascin‐C (TNC), was found in a proteomic analysis of the aqueous humor between senile cataract and RP patients with cataracts to be a candidate protein underlying capsular shrinkage pathogenesis [ 138 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Cataract is a degenerative lesion caused by optical quality loss due to lens opacity. [ 10 ] Studies have shown that inflammation after cataract surgery mainly results from mechanical injury in surgery, foreign body reaction of intraocular lens, and stimulation of membrane by residual lens epithelium, [ 1 ] which activates phospholipase A2, releases arachidonic acid, and forms prostaglandin under the catalysis of cox-enzyme, resulting in various damages such as eye pain and allergy. [ 11 , 12 ] Glucocorticoid drugs have strong anti-inflammatory effects and are widely used in the treatment of inflammation after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Phacoemulsification combined with intraocular lens implantation is the international standard surgical method for cataract, and has been popularized and applied worldwide. [ 1 ] However, cataract surgery is often accompanied by serious complications, such as endophthalmitis, corneal injury, macular cystoid edema, and secondary glaucoma, [ 2 ] which greatly affect the surgical effect and visual quality of patients. Endophthalmitis is one of the most serious complications of cataract surgery, the incidence rate in small and medium-sized ophthalmic institutions in China is 0.11%, [ 3 ] although the incidence is low, but because of the complicated environment of eye, bacterial infections and severe inflammation, it is destructive and lead to a rapid progression once happened, making it a serious threat to vision, and even lead to irreversible blindness.…”
Section: Introductionmentioning
confidence: 99%
“…There is one significant complication, which is posterior capsular opacification (PCO). This is quite rare, but some studies put the need for lens extraction due to PCO at around 11% (Fernandez, 2019); it is much more common in children than in adults (Zhang & Xie, 2020). It is a multifactorial physiological process that involves the central posterior capsule and has a serious impact on the restoration of visual function.…”
Section: The Triad Of Biocompatibility Device Functionality and Biolmentioning
confidence: 99%